Palliative nurses’ experiences of alleviating suffering and preserving dignity - Storm, Erika (Nursing ethics, 2025)
BackgroundMost patients in need of palliative care remain in their homes, thus great focus should be placed on the creation of functional palliative homecare. Suffering through an often multifaceted illness and contemplating one’s death can contribute to the loss of one’s sense of dignity, and the preservation of patient dignity is a major challenge for health professionals worldwide.AimThe aim of the study was to explore and describe nurses’ experiences of caring qualities alleviating suffering and preserving the dignity of patients in need of palliative homecare.Research designA qualitative exploratory study. In-depth semi-structured interviews as data collection method, and the qualitative content analysis of Graneheim and Lundman for data analysis. The theoretical perspective was based on Eriksson’s caritative caring theory.Participants and research contextA total of nine nurses with extensive work experience from a palliative homecare context participated in the study.Ethical considerationsThe study was conducted in accordance with the criteria set forth by the Finnish National Board on Research Integrity TENK. Research permission was granted and participants gave their written informed consent to participate in the study.FindingsOne main theme and three subthemes were found. The main theme was: Being there for the other alleviates suffering while shaping and reshaping dignity preservation in a process. The three subthemes were: (1) Being a sensitive and compassionate witness who becomes responsible, (2) Having compliance, courage, and perception in a deep presence, (3) Being calm and patient while having time for conducting skilled practical knowledge.ConclusionsCertain caring qualities are important in the dignity-preserving care of people in need of palliative homecare, and person-centeredness plays a central role in alleviating suffering. Deep and trusting caring relationships and nurses’ ability to customize the care being provided are significant in alleviating patient suffering and preserving dignity.